Financial centres' competitiveness and economic convergence: Evidence from the European Union regions. (February 2018) - Degl'Innocenti, Marta; Matousek, Roman; Tzeremes, Nickolaos G
This study analyses the gaps in financial centres' competitiveness and their impact on regional economic convergence in 23 European Union Member States during the period of the Global Financial Crisis. In particular, we explore the economic convergence and divergence patterns among regions from two different perspectives across the selected European Union Member States and within each country. From a methodological viewpoint, we apply a fully non-parametric framework to the club convergence model and address the endogeneity problem between financial centres' competitiveness and regional economic convergence. Our results show that the large and internationally-oriented financial centres experienced a diverging trend in terms of the competitiveness of financial centres' business environment during the peak of the crisis. We also find evidence that the convergence of financial centres reduces regional economic inequalities between the regions where financial centres are located. In contrast, the increase in the competitiveness of financial centres only serves to widen existing inequalities at the national level. Finally, we examine and discuss the impact of competitiveness drivers of financial centres on the convergence pattern of European Union regions.